2011
DOI: 10.3899/jrheum.110865
|View full text |Cite
|
Sign up to set email alerts
|

Scleritis: A Paradoxical Effect of Etanercept? Etanercept-associated Inflammatory Eye Disease

Abstract: Ocular inflammation is paradoxically a potential adverse effect of etanercept, even in previously uninvolved eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 25 publications
0
29
0
3
Order By: Relevance
“…However, the authors commented that their findings do not support the use of infliximab over etanercept but, rather, if a patient develops uveitis during etanercept therapy, then a change to infliximab may be warranted [49]. In a very recent study, it has been observed from data reported in the literature that forty-two cases of inflammatory eye diseases believed to be associated with the use of etanercept include 33 cases of uveitis, 8 scleritis, 1 orbital myositis [50]. These data have been obtained from 16 patients with RA, 10 with JIA, 14 with AS, and 2 with psoriatic spondyloarthropathy.…”
Section: Etanerceptmentioning
confidence: 95%
“…However, the authors commented that their findings do not support the use of infliximab over etanercept but, rather, if a patient develops uveitis during etanercept therapy, then a change to infliximab may be warranted [49]. In a very recent study, it has been observed from data reported in the literature that forty-two cases of inflammatory eye diseases believed to be associated with the use of etanercept include 33 cases of uveitis, 8 scleritis, 1 orbital myositis [50]. These data have been obtained from 16 patients with RA, 10 with JIA, 14 with AS, and 2 with psoriatic spondyloarthropathy.…”
Section: Etanerceptmentioning
confidence: 95%
“…The decrease was statistically significant with monoclonal antibodies (relative risk [RR], 7.4) but not with etanercept (RR, 0.9). Several studies suggest a causal role for etanercept in the development of inflammatory ocular disease, most notably acute anterior uveitis and scleritis, in patients without any history of predisposing inflammatory joint disease [55,56]. An analysis of a German pharmacovigilance database demonstrated a significant increase in the risk of uveitis with etanercept, compared to adalimumab or infliximab [57].…”
Section: Treatment Of Uveitis Associated With Spondyloarthritismentioning
confidence: 97%
“…33 These include TNF antagonists (adalimumab, infliximab, certolizumab, golimumab, etanercept) Anti-CD20 drugs (rituximab) Interleukin-6 receptor antagonist (tocilizumab) Interleukin-1 receptor antagonist (anakinra) Interferon-alpha Anti-CD80/86 drugs (blocks costimulatory signals from antigen-presenting cells) (abatacept) Vascular endothelial growth factor antagonists (bevacizumab, ranibizumab) (for macular edema) Among these biologic agents, experience is greatest with the TNF antagonists adalimumab and infliximab. Paradoxically, etanercept may increase the risk of uveitis and scleritis, 44 so that other TNF antagonists are preferred for ocular inflammation.…”
Section: Treatmentmentioning
confidence: 98%